Optimizing the Learning Process in Higher Education: The Six Pillars of Learning - Christian Thurn; Simona Daguati (Zeitschrift für Hochschulentwicklung)
Human learning is characterised by six process features: learning is active, constructive, emotional, self-regulated, situated, and social. However, teaching often fails to adequately honour these features, particularly within higher education. To address this issue, we explain the six pillars of learning and present examples of how to integrate them in class. As this article is intended for lecturers teaching at higher education institutions, we offer methodological guidance by providing additional material including visualizations, a didactic self-assessment tool, and posters that can be applied in diverse classroom settings, aiming to enhance teaching practices across disciplines.